Understanding Civil Servants Readiness to Work from Home: The Roles of Demographic Factors - Dyah Ayu Febriani; Fitria Ariyanti; Reza Fathurrahman (Indonesian Association for Public Administration (IAPA), 2020)
This study investigates the roles of four demographic factors, namely the types of position held, age, educational level, and length of work, behind civil servants' readiness to work from home by employing the Readiness for Organizational Change Theory (Holt et al, 2007). Primary data (n = 383) were collected from online survey with non-probabilistic sampling. The results from linear regression analysis show that individual working position, age, and educational level significantly impact their readiness to carry out telework effectively. This finding may serve as a basis for policymakers in designing proper work-from-home policies and procedures for civil servants in the future. Nevertheless, follow-up studies with different designs, theoretical frameworks, and more diverse respondents are encouraged to better understand these early findings.